Effect of the nitrogen environment on indium gallium zinc oxide thin film transistors with low temperature ultraviolet annealing - An, Kunsik (Informacije MIDEM, 2025)
This study explores the influence of nitrogen gas flow rate on the electrical characteristics of indium-gallium-zinc-oxide (IGZO) thin-film transistors (TFTs) annealed under heat-assisted UV illumination. The aim is to understand how nitrogen flow rates impact the performance of solution-processed IGZO TFTs annealed at low temperatures, which is crucial for developing highperformance devices for next-generation electronics and temperature-sensitive applications. The IGZO TFTs were fabricated on glass substrates using a bottom-gate top-contact configuration, with the IGZO thin film deposited by inkjet printing and annealed in a chamber with varying nitrogen gas flow rates (0.5, 1, 2, and 5 L/min) at 250°C for 2 hours under UV illumination. The electrical characteristics were extracted from transfer characteristics measurements. The results show that a nitrogen flow rate of 1 L/min enhances the electrical properties of IGZO TFTs, likely due to a suitable concentration of oxygen vacancies. Excessive N2 flow rates (>1 L/min) negatively impact on the TFT characteristics, while lower flow rates (<1 L/min) result in more negative threshold voltages and lower on/off current ratios. The study concludes that optimizing the nitrogen gas flow rate is critical for achieving desired TFT properties, offering a valuable tool for fine-tuning IGZO TFTs to meet specific application requirements.
Keywords: IGZO TFTs; low temperature; MEC; nitrogen annealing effect; nizka temperatura; oksidni polprevodnik; oxide semiconductor; tankoplastni tranzistor; thin film transistor; učinek dušikovega žarjenja